ASSESSMENT OF THE RESPIRATORY FUNCTION AND SELECTED CHARACTERISTICS OF HEALTHY LIFESTYLE - Boуko D.M.; Boуko M.G.; Bobyrevа L.E.; Sobol, A.A.; Boyko, O.S. (World of Medicine and Biology, 2012)
It is extremely important for modern society is the problem of respiratory diseases. It is determine a lot of attention of the World Health Organization to the pathology of the lungs and the use of tobacco products. The goal was to investigate among the study participants the level of sports activities, state of the problem of tobacco use, particularly cigarette smoking and lung health by spirometry, and early symptoms of chronic obstructive pulmonary disease based on a standard questionnaire (GOLD). This research project is positioned as an analytical cross-sectional pilot study. Conducted with the participation of 156 people (age (Me) 21.0), the volunteer who expressed a desire to fill out a questionnaire to determine lung function by spirometry. Among the study participants revealed a fairly large proportion of active tobacco users (42%), that indicating a significant level of interest for health status in smokers. In the group of persons regularly engaged in physical training detected almost 45% of active smokers, suggesting the existence of a significant layer of “healthy smokers” in young adults. The total experience of smoking on the level of (Me) 1.5 number of pack years among those aged (Me) 21.0 was associated with significant changes in FEV1/FVC.